Biofluids profile of α-Klotho in patients with Parkinson's disease. (September 2021) - Sancesario, Giulia Maria; Di Lazzaro, Giulia; Grillo, Piergiorgio; Biticchi, Benedetta; Giannella, Emilia; Alwardat, Mohammad; Pieri, Massimo; Bernardini, Sergio; Mercuri, Nicola Biagio; Pisani, Antonio; Schirinzi, Tommaso
Abstract: We measured α-Klotho in CSF and serum of PD patients at early stage of the disease, finding two distinct pools, the first increased, the second reduced. CSF α-Klotho was inversely associated with CSF α-synuclein levels. Our preliminary results suggest α-Klotho as potential biomarker or therapeutic target in PD. Highlights: The anti-aging protein α-Klotho pathway is scarcely explored in vivo in PD . CSF α-Klotho was higher in PD patients and inversely correlated with CSF α-synuclein. Serum α-Klotho was reduced in PD patients independently from CSF markers. α-Klotho may be a biomarker or candidate target for neuroprotection in PD.